HUBUNGAN AKTIVITAS FISIK DENGAN KEJADIAN DISMENOREA PADA SISWI SEKOLAH MENENGAH PERTAMA DAN SEKOLAH MENENGAH ATAS ISLAM HASMI - Asti Meiana (2023)
The rate of dysmenorrhea in Indonesia has an average of 45-95% which occurs in the productive period. In accordance with the high prevalence of dysmenorrhea affecting the daily activities of young women to be hampered. One of the factors that can reduce dysmenorrhea pain is by doing vigorous activities or physical exercise. Physical activity increases endorphins levels and suppresses prostaglandins there by reducing dysmenorrhea pain. This study aims to determine the relationship between physical activity and the incidance of dysmenorrhea. This research was conducted at HASMI Islamic Middle School and High School, with the correlation method of cross sectional approach. as many as 95 female students were involved in this study. Data collection used the Physical Activity Questionnaire Short Form (IPAQ-SF) to measure the level of physical activity and the numeric rating scale (NRS) to measure the incidence of dysmenorrhea. Data analysis was performed using univariate analysis, normality test, and bivariate analysis. This study used SPSS 25 and the results obtained were p = 0.00 with a correlation coefficient of -0.516 which means that there is a strong relationship between physical activity and the incidence of dysmenorrhea. In conclusion, there is a significant relationship between physical activity and the incidence of dysmenorrhea which is not unidirectional.